Consistent downregulation of the cleft lip/palate-associated genes IRF6 and GRHL3 in carcinomas - Parisi, Ludovica; Mockenhaupt, Carolin; Rihs, Silvia; Mansour, Farah; Katsaros, Christos; Degen, Martin (Frontiers in Oncology, 2022)
Interferon Regulatory Factor 6 (IRF6) and Grainyhead Like Transcription Factor 3 (GRHL3) are transcription factors that orchestrate gene regulatory networks required for the balance between keratinocyte differentiation and proliferation. Absence of either protein results in the lack of a normal stratified epidermis with keratinocytes failing to stop proliferating and to terminally differentiate. Numerous pathological variants within IRF6 and GRHL3 have been identified in orofacial cleft-affected individuals and expression of the two transcription factors has been found to be often dysregulated in cancers. However, whether orofacial cleft-associated IRF6 and GRHL3 variants in patients might also affect their cancer risk later in life, is not clear yet. The fact that the role of IRF6 and GRHL3 in cancer remains controversial makes this question even more challenging. Some studies identified IRF6 and GRHL3 as oncogenes, while others could attribute tumor suppressive functions to them. Trying to solve this apparent conundrum, we herein aimed to characterize IRF6 and GRHL3 function in various types of carcinomas. We screened multiple cancer and normal cell lines for their expression, and subsequently proceeded with functional assays in cancer cell lines. Our data uncovered consistent downregulation of IRF6 and GRHL3 in all types of carcinomas analyzed. Reduced levels of IRF6 and GRHL3 were found to be associated with several tumorigenic properties, such as enhanced cell proliferation, epithelial mesenchymal transition, migration and reduced differentiation capacity. Based on our findings, IRF6 and GRHL3 can be considered as tumor suppressor genes in various carcinomas, which makes them potential common etiological factors for cancer and CLP in a fraction of CLP-affected patients.